Perioperative Management of Patients with Extra Axial Tumors in the Region Suprasella et causa Suspected Pituitary Macroadenoma Undergoing Tumor Resection Craniotomy Procedures Endonasal Transphenoid with Postoperative Diabetes Insipidus Complications - Tjokorda Gde Agung Senapathi; Cung Flavyanto, Eugenius Silvester (HM Publisher, 2023)
Introduction: Perioperative management of a patient with a pituitary macroadenoma involves a complex set of procedures, including careful clinical evaluation, decision making regarding the surgical strategy, preparation of the patient before surgery, execution of the operation with the correct technique, and care.post operation effective. Case presentation: A 52-year-old female patient with the diagnosis of extra axial tumor R. Suprasella ec susp pituitary macroadenoma, the plan is to perform craniotomy for transphenoid endonasal tumor resection. Induction with TCI propofol and preoxygenation. For analgesia can be given fentanyl 2-5 g/kg during induction, but before intubation. Ensure adequate neuromuscular blockade prior to intubation to avoid coughing/straining. Intubation with a videolaryngoscope is the technique we use to secure the airway. The position of the patient will depend on the location of the tumor. Maintain anesthesia with TCI propofol target effect 2-3 µg/kg/min, dexmedetomidine 0.2-0.7 mcg/kg/hour, and intermittent fentanyl 0.5-1 mg/kg/hour. Use light hyperventilation (PaCO2 30-35 mm Hg). Maintain euvolemia (Ringer Fundin/iso osmolar fluid) and neuromuscular relaxation. Conclusion: In these cases the anesthetic technique must be targeted towards hemodynamic stability, maintenance of adequate cerebral oxygenation and normal intracranial pressure. Postoperative care must also be considered considering the bleeding complications due to large blood vessel trauma and diabetes insipidus which often occurs post operation.